Exploring the Asymmetric Characteristics of a Double Gate MOSFET with Linearly Graded Binary Metal Alloy Gate Electrode for Enhanced Performance. Issue 6 (1st November 2016) - Bagga, Navjeet; Sarkhel, Saheli; Sarkar, Subir Kumar
ABSTRACT: The present boon in the research field of nanoscale device physics is attributed to a large extent by the development of non-conventional multiple gate MOS devices due to increased device packing density and enhanced gate electrostatic control over the channel. In this work, we have investigated the attributes of an asymmetric Double Gate metal oxide semiconductor field effect transistor (MOSFET) incorporating the novel theory of work function engineering by the continuous horizontal variation of mole fraction in a binary metal alloy gate in a fully depleted Double Gate MOSFET. A two-dimensional analytical modeling of this Linearly Graded Asymmetric Double Gate MOSFET structure has been done to formulate a simplified expression for short channel threshold voltage, and an overall performance analysis of our proposed device has been presented to establish the superiority of our proposed structure in terms of superior short channel effect mitigation and a significant reduction in threshold voltage. The results obtained from our analytical analysis are found to be in good agreement with the simulation results, thereby, establishing the accuracy of our model.